Microwave enhanced catalytic conversion of canola-based methyl ester: Optimization and parametric study - Bokhari, A. (Elsevier, 2019)
The demand for energy resources and environmental issues are driving the global development of renewable energy. Biodiesel (alkyl esters) from vegetable oils or animal fats via transesterification is said to be the next promising bioenergy that can substitute petroleum-derived diesel fuel. Transesterification is a catalyzed process; hence, homogeneous catalysts are employed for biodiesel production. Unfortunately, over the past few years, many problems related to homogeneous catalysts have been reported. The purification process of free fatty acids tends to prolong the production and thus results in further complications, thus stimulating the conception of heterogeneous catalyzed transesterification. Despite the success of various heterogeneous catalysts, many are not viable for industrial usage as most of the catalysts are expensive and additional preparation methods are needed. Some of the heterogeneous catalysts widely used by the industries are ZnO, KNO3, and CaO. Among these three heterogeneous catalysts, calcium oxide (CaO) shows great capability in catalyzing the reaction. Besides that, canola oil is found abundantly in Malaysia. In addition, microwave-assisted techniques can save a lot of time and energy. Therefore, in this chapter, the effect of reaction time, alcohol-to-oil ratio, amount of catalyst, and microwave frequency are investigated under microwave conditions. Based on the optimized condition, the biodiesel yield is 77 wt. The optimization is done by using Response Surface Methodology in which central composite design is used to determine the significance level and interaction effect of these parameters. In conclusion, this research shows that canola oil has a great potential to be a feedstock to produce biodiesel. Â© 2019 Elsevier Ltd. All rights reserved.